2014
DOI: 10.1177/1355819614557299
|View full text |Cite
|
Sign up to set email alerts
|

Developing effective feedback on quality of anaesthetic care: what are its most valuable characteristics from a clinical perspective?

Abstract: For clinicians to engage with effective quality monitoring and feedback, the perceived local relevance of indicators and trust in the credibility of the resulting data are paramount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
3
20
0
1
Order By: Relevance
“…Articles discussing the importance of information dissemination in A&F rarely describe whether this information relates to the understanding of the purpose of A&F or to the understanding of EBP (D'Lima et al . ). It is clear that understanding the purpose of A&F is important for nurses to partake in the process.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Articles discussing the importance of information dissemination in A&F rarely describe whether this information relates to the understanding of the purpose of A&F or to the understanding of EBP (D'Lima et al . ). It is clear that understanding the purpose of A&F is important for nurses to partake in the process.…”
Section: Discussionmentioning
confidence: 97%
“…Regardless, the idea that a better understanding of its purpose leads to improved effectiveness of A&F does not seem to have been well discussed in the literature. Articles discussing the importance of information dissemination in A&F rarely describe whether this information relates to the ª 2016 John Wiley & Sons Ltd understanding of the purpose of A&F or to the understanding of EBP (D'Lima et al 2015). It is clear that understanding the purpose of A&F is important for nurses to partake in the process.…”
Section: Understanding Of the Purpose Of Aandfmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Benn and colleagues on performance feedback to clinicians emphasises the importance of tailoring interventions and information to the specific clinical setting (in this case, anaesthesia) in order to get engagement and commitment to safety measurement systems. 41 Despite being highlighted as a gap in the 2010 patient safety research call, few high-quality responses were received on the topic of patient involvement in patient safety. However, there were some important contributions, including a study by Birks and colleagues on 'open disclosure' to patients who have been harmed while receiving health care.…”
Section: What These New Studies Addmentioning
confidence: 99%
“…12 17--23 Analysis of the predictors of perceived usefulness of data on quality of care for anaesthetists has shown that the most important characteristics for effective feedback are 1) the local relevance of quality indicators, and 2) the perceived credibility of the data. 24 Evaluations of feedback have been conducted in other clinical areas but not in a perioperative unit using personalised, individualised feedback for anaesthetists, based on quality indicators measured in the recovery room. 23 25--27 We implemented and evaluated one such intervention in the anaesthetics department of a large teaching hospital, demonstrating positive impact upon the rated quality of feedback available to anaesthetists, in addition to patient--reported quality of recovery indicators.…”
mentioning
confidence: 99%